2020
DOI: 10.1038/s41467-020-14493-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular elucidating of an unusual growth mechanism for polycyclic aromatic hydrocarbons in confined space

Abstract: Extension and clustering of polycyclic aromatic hydrocarbons (PAHs) are key mechanistic steps for coking and deactivation in catalysis reactions. However, no unambiguous mechanistic picture exists on molecule-resolved PAHs speciation and evolution, due to the immense experimental challenges in deciphering the complex PAHs structures. Herein, we report an effective strategy through integrating a high resolution MALDI FT-ICR mass spectrometry with isotope labeling technique. With this strategy, a complete route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 60 publications
2
93
0
1
Order By: Relevance
“…Besides GC-MS, the matrix-assisted laser desorption/ionization Fourier-transform ion cyclotron resonance mass spectrometer (MALDI FT-ICR MS) was also used to obtain the complementary spectrum for the evolution of coke species 19 ranged from 300 to 1600 Da confined in CHA cavity during steam cracking, as shown in Fig. 4b .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides GC-MS, the matrix-assisted laser desorption/ionization Fourier-transform ion cyclotron resonance mass spectrometer (MALDI FT-ICR MS) was also used to obtain the complementary spectrum for the evolution of coke species 19 ranged from 300 to 1600 Da confined in CHA cavity during steam cracking, as shown in Fig. 4b .…”
Section: Resultsmentioning
confidence: 99%
“…These hydrocarbon pool species (HCPs), typically including the methyled-benzene carbocations 10 , 11 and cyclopentadienyl species 12 , 13 , are decisive for light olefins selectivity, owning to the altering of acidity 14 , reaction paths 15 , kinetics 8 , 9 , molecular transport 16 , and among others. However, the HCPs are also coke precursors that can readily evolve to polycyclic aromatic hydrocarbons (PAHs), the typical coke species, through cyclization 17 and cross-linked mechanism 18 , 19 , accelerating catalyst deactivation 20 . Therefore, such dual-role of HCPs impedes achieving superior light olefins selectivity while maintaining long catalyst lifetime in MTO over zeolitic catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adsorption bands at ~561 nm (PH n + ) and ~640 nm (PYR n + ) are relatively unconspicuous in the small crystal. It has been recently shown that carbonaceous species located in adjacent cavities can be further connected through windows during reaction to form heavier carbonaceous species 48 , 55 . As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The organic compounds were extracted by addition of 1 mL CH 2 Cl 2 with 100 ppm internal standard C 2 Cl 6 for 1 h. Analysis of the extracted phase was performed on an Agilent 7890A/5975C GC/MS instrument, equipped with a HP-5 capillary column and FID detector. Then the carbonaceous species in the extracted phase were then mixed with matrix 1,8,9-anthracenetriol and further analyzed by a 15-T SolariX XR FT-ICR MS (Bruker Daltonics) 55 . The instrument was equipped with a Nd:YAG laser ( λ = 335 nm) and a time-of-flight mass analyzer in reflection mode.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the major chemical that produced by a flame-proof door when it is on fire was PAHs, VOCs, SO2 and cyanide, they were well-known carcinogens for a long time. All the combustion byproducts in our study were researched in many other kinds of research [50][51][52]. Research showed that in hundreds of lung cancer cases there was a clear trend of increasing risk of lung cancer with increasing cumulative exposure to PAHs [53].…”
Section: Discussionmentioning
confidence: 83%